The treatment of functional constipation significantly increased quality of life in children aged 4-17 years - Erdur, Barış; Ayar, Murat (Turkish Journal of Gastroenterology, 2020)
Background/Aims: In this study, it was aimed to investigate the effect of 6-week treatment on quality of life in 4-17-year-old children with functional constipation. Materials and Methods: The children 4-17 years old diagnosed as functional constipation according to Rome IV criteria, between June and December 2018 were included in the study. KINDL scales were applied to patients and their parents before starting treatment for 6 weeks and after the end of the treatment. Results: The study was completed with 42 patients. The majority of the patients (54,8%) were female cases and the general part of them (45,2%) were between 4-6 years old. The age at onset of constipation was found to be 5,19±3,658 years. Total KINDL scores of both children and parents were lower before the treatment. Significant improvement was observed in the symptoms of constipation after 6 weeks of treatment. There was a statistically significant (p<0,05) increase in children’s subgroup and total KINDL scores after treatment. Parental subgroup and total KINDL scores also showed a statistically significant (p<0,05) increase after treatment. The treatment of functional constipation was found to be highly effective with the eyes of both children and parents in improving the quality of life. (Eta value, η2.>0,25) Conclusion: A significant increase was observed in all areas of life quality and total score in children with functional constipation after a regular treatment. We think that the treatment of children with functional constipation will significantly improve their quality of life